The isotopic signature and distribution of particulate iron in the North Atlantic Ocean - Revels, B.; Ohnemus, Daniel C.; Lam, Phoebe J.; Conway, Tim M.; John, Seth G. (Deep Sea Research Part II: Topical Studies in Oceanography, 2015)
ISSN:0967-0645